Data in the Domain of School Education – Secondary School: Present situation, New Developments, and Future Requirements - Petra Stanat; Hans Döbert (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Research on school education is exceptionally active at present. This heightened level of activity is partly due to the realization that, compared to other countries, Germany knows very little about its school system. Before the results from the first cycle of PISA (Programme for International Student Assessment) were published at the end of 2001, for example, even the proportion of immigrant students attending German schools was largely unknown (Baumert and Schümer 2001). Although the situation has changed tremendously over the last 10 years, many questions remain open. One of the major research gaps pertains to how students' competencies and other aspects of educational success develop over time and across different stages of the education system. Similarly, information on factors shaping these developments is lacking. This is particularly the case for process factors within schools, classrooms, and families that affect student learning. Although considerable progress has been made in capturing cognitive competencies and skills, moreover, little is known about how they unfold over time. Also, the role "soft-skills," such as social competencies, play as determinants and outcomes of educational processes is largely unclear. To provide a basis for exploring these and other issues, it is necessary to make existing data sets available to researchers and to generate additional data sets with improved research designs and instrumentation.
Keywords: 330